IDENTIFIKASI BAKTERI Escherichia coli PENGHASIL EXTENDED SPECTRUM β-LACTAMASE PADA DAGING SAPI YANG DIJUAL DI PASAR BASAH MENGGUNAKAN METODE VITEK-2 PENELITIAN EKSPLORATIF LABORATORIK - RISI CICILIA, 061614253002 (2018)
This study aims to phenotypically identify and confirm the presence of ESBL-producing Escherichia coli in the swab surface samples of beef using VITEK-2 method. Swab samples were taken from five wet markets: Pucang market, Wonokromo market, Keputran market, Pabean market, and Manukan market; 10 swab samples of beef were collected from each market. Then, isolation and identification in terms of bacteria using selective media and biochemical test were conducted. Resistance testing using disc diffusion method was performed on 6 types of antibiotics: Ampicillin, Cefazolin, Ceftriaxone, Cefotaxime, Ceftazidime, and Tetracyclin. Positive isolates resistant to ≥ 2 types of β-Lactam antibiotics using disc diffusion method then were tested using VITEK-2 method. Positive samples containing Escherichia coli are found in 29 samples out of 50 swab samples. Of the 29 Escherichia coli isolates, 17 isolates are found resistant to the disc diffusion method. After testing those 17 isolates using VITEK-2, 5% (1/17) of ESBL-producing Escherichia coli are obtained. Besides, this study also reveals that 35% (6/17) of the Escherichia coli are positive multidrug resistance. Those E.coli are found to be resistant towards Amoxycillin of 35% (6/17), Gentamycin of 5% (1/17), Ciprofloxacin of 35% (6/17), Trimethophrim- Sulfamethoxazole of 35% (6/17), and Ampicillin-sulbactam of 5% (1/17).